From Performance to Pedagogy: Insights Into Theatre Directing for Educational Purposes - Prusdianto, Prusdianto; Masri, Andi Sulfana; Jazuli, Muhammad; Syakhruni, Syakhruni; Cahyono, Agus; Arifin, Irfan (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study investigates the pedagogical foundations and contextual relevance of theatre directing education within teacher preparation programs, with a particular focus on how directing practices align with contemporary teaching and learning demands. Employing a mixed-methods needs analysis, data were collected through curriculum analysis, classroom observation, surveys, and semi-structured interviews with lecturers, pre-service art teachers, and in-service educators. Findings reveal that directing instruction in higher education tends to privilege performance production and technical skills, while its pedagogical implications for school settings remain underexplored. Additionally, humanitarian and socio-emotional elements of theatre, which could enhance learner engagement and inclusive education, were inconsistently embedded in course design. These outcomes underscore the importance of reframing directing education as a learner-centred pedagogical practice that integrates critical reflection, contextual responsiveness, and educational theory. By positioning theatre not only as an artistic endeavour but also as a vehicle for meaningful teaching and learning, this research contributes to theoretical and practical discussions in teacher education and arts-based pedagogies.